Pre-Hispanic anthropogenic wetlands in the upper Ica drainage, south-central Andes: dating and context. (October 2022) - Lane, Kevin; Beresford-Jones, David; Coll, Luis; Marsh, Erik; Scaife, Rob; Greco, Catriel; Oros, Oliver Huaman; Herrera, Alexander; Grant, Jennifer; French, Charles
Abstract: Abstract : Humans have engineered their environments throughout the Holocene, especially in the construction of hydraulic infrastructure. In many regions, however, this infrastructure is difficult to date, including the vestiges of water-management systems in the Andean highlands. Focusing on silt reservoirs in the upper Ica drainage, Peru, the authors use cores and radiocarbon dates to demonstrate the pre-Hispanic construction of walls to enhance and expand wetlands for camelid pasture. Interventions dated to the Inca period (AD 1400–1532) indicate an intensification of investment in hydraulic infrastructure to expand production capacity in support of the state. The results are discussed in the context of the hydraulic strategies of other states and empires.